2018
DOI: 10.1080/00207543.2018.1497313
|View full text |Cite
|
Sign up to set email alerts
|

Workload control in dual-resource constrained high-variety shops: an assessment by simulation

Abstract: Workload Control (WLC) seeks to align capacity with demand, where capacity is typically assumed to be restricted by a single constraintmachine capacity. In practice however, shops are often restricted by dual resource constraints: labor and machines. This study therefore uses simulation to investigate the performance of WLC in Dual Resource Constrained (DRC) highvariety shops with fully interchangeable labor. By considering several environmental factors and different labor assignment and dispatching rules, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…There are mainly two types of When Rules applied in the literature: a 'centralized' rule that transfers a worker each time a job is completed and a 'decentralized' rule that transfers a worker after completing all jobs at the current station. The centralized rule tends to outperform the decentralized When Rule but at the expense of an increase in the number of worker transfers (Thürer et al, 2019). Meanwhile, it has been shown that incorporating future workload information into the When Rule does not improve performance enough to impact a manager's decisions (Fredendall et al 1996).…”
Section: Worker Assignmentmentioning
confidence: 99%
See 3 more Smart Citations
“…There are mainly two types of When Rules applied in the literature: a 'centralized' rule that transfers a worker each time a job is completed and a 'decentralized' rule that transfers a worker after completing all jobs at the current station. The centralized rule tends to outperform the decentralized When Rule but at the expense of an increase in the number of worker transfers (Thürer et al, 2019). Meanwhile, it has been shown that incorporating future workload information into the When Rule does not improve performance enough to impact a manager's decisions (Fredendall et al 1996).…”
Section: Worker Assignmentmentioning
confidence: 99%
“…Only if a worker is assigned to a station is capacity realized and orders can be processed. We use only one staffing level since the impact of different staffing levels has recently been assessed in Thürer et al (2019). We focus on the lowest staffing level from previous studies, i.e.…”
Section: Overview Of Modeled Shop and Job Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the release method, the research evaluates the due date assignation considering forecasting system to maximize the on-time deliveries [16,17].…”
Section: Literature Overviewmentioning
confidence: 99%